2001
DOI: 10.1159/000051788
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Syringomas with Calcium Deposits in a Young Woman with Down’s Syndrome

Abstract: Eruptive syringomas are uncommon in the general population. We describe here an 18-year-old female, affected by Down’s syndrome, who presented with an abrupt eruption of small skin-colored or reddish papules on the face, neck and limbs. Light microscopy allowed us to diagnose syringomas, whereas the study of the ultrastructural features revealed calcium deposits in many lumina and also in the mitochondria. This observation confirms the hypothesis that the syringeal structure plays a role in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…24 Butterworth et al described syringomas in 18.5% of 200 institutionalized DS patients, with a prevalence of 26% among female and 13% among male patients. 24 The same authors have also noted MICC in association with syringomas in DS, thus supporting the hypothesis that syringeal structures may play an important role in the pathogenesis of MICC in DS. 24 The same authors have also noted MICC in association with syringomas in DS, thus supporting the hypothesis that syringeal structures may play an important role in the pathogenesis of MICC in DS.…”
Section: Syringomasmentioning
confidence: 99%
“…24 Butterworth et al described syringomas in 18.5% of 200 institutionalized DS patients, with a prevalence of 26% among female and 13% among male patients. 24 The same authors have also noted MICC in association with syringomas in DS, thus supporting the hypothesis that syringeal structures may play an important role in the pathogenesis of MICC in DS. 24 The same authors have also noted MICC in association with syringomas in DS, thus supporting the hypothesis that syringeal structures may play an important role in the pathogenesis of MICC in DS.…”
Section: Syringomasmentioning
confidence: 99%
“…Surgical excision has shown to be beneficial, as it can provide a symptomatic relief. However, because calcinosis cutis limits are not always well defined and surgical trauma itself may induce calcification, a recurrence of the lesions may occur 1–3,5–13 …”
Section: Discussionmentioning
confidence: 99%
“…SCN are usually classified as an idiopathic entity, but in our patient, calcified lesions were associated with multiple skin‐coloured lesions of upper and lower eyelids which have preceded them by several years and histopathologically correspond to syringomas. Syringomas have been previously described in association with idiopathic calcinosis cutis especially in patients with Down's syndrome 9 but also in healthy patients 10 . But to our knowledge, syringomas have never been described in association with SCN.…”
mentioning
confidence: 85%
“…Schepis et al . stated that syringeal ductal structures play a role in calcium deposit since ultrastructural study revealed calcium deposits in many lumina and in the mitochondria in a trisomic patient with eruptive syringomas 9 . In SCN without associated syringomas, the cause of calcium deposit is not well established.…”
mentioning
confidence: 99%